The Implementation of the Government Rice Reserve Food Assistance Program for Low-Income Households in Padang Pariaman Regency - Anisfi Oktaviani; Adil Mubarak (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Food assistance policies constitute an important social protection instrument for low-income households, particularly in regions where access to staple foods remains vulnerable. This study analyzed the implementation of the Government Rice Reserve (Cadangan Beras Pemerintah [CBP]) Rice Food Assistance Program for low-income households in Padang Pariaman Regency. A qualitative approach with a descriptive case-based design was employed. Informants were selected through purposive and snowball sampling and included representatives from Perum BULOG, the Social Affairs Office of Padang Pariaman Regency, village governments, subdistrict social welfare workers, an academic expert, beneficiaries, and non-beneficiaries. Data were collected through interviews, field observations, and documentation and analyzed using an interactive qualitative model comprising data collection, data condensation, data display, and conclusion drawing. The findings indicate that the program was implemented through structured planning, task allocation, monitoring, and evaluation. Although the program supported low-income households in meeting their basic food needs, its implementation remained suboptimal because of inaccurate beneficiary data, limited access to the distribution application, insufficient field supervision personnel, and coordination mechanisms that continued to rely heavily on WhatsApp groups. The study concludes that the effectiveness, accuracy, and equity of rice assistance distribution depend on reliable beneficiary data, accessible digital infrastructure, adequate supervisory capacity, and integrated interinstitutional coordination. These findings contribute to the literature on public policy implementation and extend understanding of food assistance governance at the local level. The study provides practical implications for strengthening beneficiary data updating, expanding digital access for local officers, increasing field supervision capacity, and developing a more integrated coordination system to ensure that rice assistance reaches eligible households more accurately, fairly, and humanely.